Evaluation of clinical parameters of patients with Covid-19 pneumonia on admission and medications used for their comorbidities - Civan, Murat; Haciosman, Hasan (Asian Journal of Medical Sciences, 2021)
Background: Risk factors and molecular mechanisms of severe respiratory involvement of Covid-19 are investigated more intensely and some doubts about non-steroidal antiinflammatory drugs (NSAID) and renin-angiotensin-aldosterone system (RAAS) inhibitors has also emerged. Aims and Objective: We aimed to detect potential associations between medications taken regularly for comorbid diseases before the diagnosis of Covid-19 pneumonia and demographic or clinical features on admission. Materials and Methods: Patients diagnosed with pneumonia between March 11th, 2020 and April 15th, 2020 in emergency, internal medicine and cardiology outpatient clinics were recruited and their clinical and demographic features including blood tests, oxygen saturations (SO2) along with degree of lung infiltrations in computed tomography on admission were analyzed in regard to their medications used regularly. Results: Angiotensin converting enzyme inhibitors (ACE inh.) or angiotensin receptor blockers (ARB) users were older than no-ACE inh./ARB group and had significantly lower SO2 on admission, whereas NSAID users with Covid-19 displayed a marked female predominance and lower hemoglobin levels than no-NSAID group. Proton pump inhibitor (PPI) users had also a significant female predominance and older age with lower hemoglobin levels. Lastly, antiaggregant users with Covid-19 had a lower SO2 on admission and overall, cases with regular drug intake were markedly associated with older age. Conclusion: Noteworthy associations were observed between demographic and clinical features on admission for Covid-19 pneumonia and major drug groups used regularly including RAAS inhibitors, NSAIDs and proton pump inhibitors.